Entrepreneurial Inclination: Reviewing Literature for Entrepreneurship among Tribal Women - Prof. Lurai Rongmei; Prof. A.L Ghosh (International Journal of Engineering and Management Research, 2023)
Purpose- As stated earlier, the goal of this research is to give a complete overview of the existing literature on entrepreneurial inclination. The paper examines and reviews the different definitions and terminologies used by previous scholars towards defining entrepreneurial inclination which includes definition of entrepreneur, women entrepreneur, entrepreneurship, entrepreneurial intention, entrepreneurial inclination, entrepreneurship education, entrepreneurial culture and their views. The review found that the term ‘entrepreneurial inclination’ is of psychological phenomenon which influences by many other factors for a woman in deciding entrepreneurial behaviour. The study identified and addressed the causes of inadequate supply of entrepreneurship among tribal women. The study provide suggestions putting forward the policy measures for inclusive entrepreneurship. Methodology- Uses a desk-based approach. Findings- If one wants to understand the motivations of an entrepreneur, one must first grasp the individual's psychological characteristics. Based on what we've learned from the study, we can begin a discussion about how we can help indigenous women develop their entrepreneurial skills and abilities so that they may pursue their dreams of starting up a business. Research Limitations/Implications- The research is summarised in this paper. The lack of information on one's aptitude for entrepreneurship lays the groundwork for more study. Originality- Tribal women's entrepreneurial inclination is summarised in this article, and the likely policy measures needed to understand and foster entrepreneurship among tribal people are addressed. Paper Type- Literature Review.